2011
DOI: 10.1371/journal.pbio.1001222
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Motions Direct Electrons along Human Microsomal P450 Chains

Abstract: Directional electron transfer through biological redox chains can be achieved by coupling reaction chemistry to conformational changes in individual redox enzymes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
87
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(100 citation statements)
references
References 36 publications
12
87
1
Order By: Relevance
“…Because previous ensemble studies could only report on the averaged protein conformational distributions, and could not provide insight into the conformational dynamics (34,37,38,40), our study represents a significant advance and provides an interesting perspective on how CaM may regulate nNOSr electron transfer reactions through its control of protein conformational behavior.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because previous ensemble studies could only report on the averaged protein conformational distributions, and could not provide insight into the conformational dynamics (34,37,38,40), our study represents a significant advance and provides an interesting perspective on how CaM may regulate nNOSr electron transfer reactions through its control of protein conformational behavior.…”
Section: Discussionmentioning
confidence: 99%
“…two to four discreet conformational populations in NOS enzymes and in related flavoproteins, and in some cases, have also estimated the distances between the bound FAD and FMN cofactors in the different species (26,36,37,39,40), and furthermore, have confirmed that CaM shifts the NOS population distribution toward more open conformations (34,36,45). Although valuable, such ensemble-averaged results about conformational states cannot explain how electrons transfer through these enzymes, or how CaM increases the electron flux in NOS, because answering these questions requires a coordinate understanding of the dynamics of the conformational fluctuations.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of 2Ј-AMP (or NADP(H)), this region of the polypeptide may be less ordered in A287P/P228L/A503V, thus rendering the two subdomains more easily separable and allowing the polypeptide to be more easily degraded by trypsin. Furthermore, it has been shown that the POR molecule adopts two conformations, open and closed forms (33,34), and it has been suggested that binding NADP(H)/2Ј-AMP favors the closed form (33)(34)(35). In the absence or diminished occupancy of the nucleotide, the POR molecule would more likely be in an open state, which would be more susceptible to trypsinolysis.…”
Section: Structural Characterization Of A287p Por In the Vicinity Of mentioning
confidence: 99%
“…It is not clear why the ΔN‐CPR should exhibit higher rates, but presumably loss of the MAD makes CPR more freely accessible to interact with cytochrome c , which, unlike the natural CYP redox partner of CPR, is small, not membrane‐bound and freely diffusible in aqueous medium. It is known that CPR adopts multiple conformations and that each will react differently with cytochrome c 54, 55. Truncation of the MAD in the ΔN‐CPR is expected to affect the conformational landscape of CPR.…”
Section: Discussionmentioning
confidence: 99%